Self, others and the state : relations of criminal responsibility / Arlie Loughnan. - Loughnan, Arlie (Law in context., 2020)
Criminal responsibility is now central to criminal law, but it is in need of re-examination. In the context of Australian criminal laws, Self, Others and the State reassesses the general assumptions made about the rise to prominence of criminal responsibility in the period since around the turn of the twentieth century. It reconsiders the role of criminal responsibility in criminal law, arguing that criminal responsibility is significant because it organises key sets of relations - between self, others and the state - as relations of responsibility. Detailed studies of decisive moments and developments since the turn of the twentieth century, and original explorations of relations of responsibility, expose the complexity and dynamism of criminal responsibility and reveal that it is the means by which matters of subjectivity, relationality and power make themselves felt in the criminal law.